Marketing de guerrilla en la microindustria de calzado de cuero - Barbosa Vega, Jonathan Valentín (2017)
The present project aims to contribute to the micro industry in shoes, allowing it to increase its sales volumes and make its products known to the population in Latacunga in a different way than conventional with the application of guerrilla marketing strategy which will also help micro-industry in shoes is more competitive within the market. We can discover that some of the reasons why industry in shoes does not apply this type of marketing is because of their total inexperience of the same or the lack of academic preparation that exist in the owners of the micro industry in shoes, that is through the creation of the strategy done a diagnosis of the internal and external situation of the micro-industries will have a guide that facilitates the execution of these strategies. The researching project will have the application of techniques and tools that will contribute the development of this, which will be of great importance for their respective execution, the researching project has as its purpose to become a reference for micro industry of footwear leading them to be competitive within a changing market.